Toe and earlobe capillary blood sampling for lactate threshold determination in rowing - Forsyth, J. J.; Mann, C.; Felix, J. (International Journal of Sports Physiology and Performance, 2012)
Purpose: In rowing ergometry, blood for determining lactate concentration can be removed from the toe tip without the rower having to stop. The purpose of the study was to examine whether sampling blood from the toe versus the earlobe would affect lactate threshold (Tlac) determination. Methods: Ten physically active males (mean ± age 21.2 ± 2.3 y; stature 179.2 ± 7.5 cm; body mass 81.7 ± 12.7 kg) completed a multistage, 3 min incremental protocol on the Concept II rowing ergometer. Blood was sampled simultaneously from the toe tip and earlobe between stages. Three different methods were used to determine Tlac. Results: There were wider variations due to the method of Tlac determination than due to the sample site; for example, ANOVA results for power output were F(1.25, 11.25) = 11.385, P = .004 for method and F(1, 9) = 0.633, P = .45 for site. The greatest differences in Tlac due to sample site in rowing occurred when Tlac was determined using an increase in blood lactate concentration by >1 mmol/L from baseline (Tlac<Laplace-Operator>1). Conclusions: The toe tip can be used as a suitable sample site for blood collection during rowing ergometry, but caution is needed when using the earlobe and toe tip interchangeably to prescribe training intensities based on Tlac, especially when using Tlac<Laplace-Operator>)1 or at lower concentrations of lactate.